Clitoria ternatea (Linn.) flower extract attenuates vascular dysfunction and cardiac hypertrophy via modulation of Ang II/AT1R/TGF‐β1 cascade in hypertensive rats. (19th October 2021) - Maneesai, Putcharawipa; Chaihongsa, Nisita; Iampanichakul, Metee; Meephat, Sariya; Prasatthong, Patoomporn; Bunbupha, Sarawoot; Wunpathe, Chutamas; Pakdeechote, Poungrat
Abstract: BACKGROUND: Clitoria ternatea (CT) (the Fabaceae family) has been reported to elicit several biological responses, such as anti‐inflammation and anti‐depression effects. This study evaluated the effect of CT flower extract on blood pressure, vascular function, and left ventricular hypertrophy in a two‐kidney, one‐clip (2K‐1C) rat model. Hypertensive rats were treated with CT extract at various doses (100, 300, or 500 mg kg −1  day −1 ) or losartan (10 mg kg −1  day −1 ) for 4 weeks ( n  = 8/group). RESULTS: CT extract reduced blood pressure in a dose‐dependent manner, and CT extract at a dose of 300 mg kg −1 was an effective concentration ( P  < 0.05). Augmentation of contractile responses to electrical field stimulation and impairment of vascular responses to acetylcholine in mesenteric vascular beds and aortic rings of 2K‐1C rats were suppressed by treatment with CT extract or losartan ( P  < 0.05). Serum angiotensin‐converting enzyme activity and plasma angiotensin II concentration were high in 2K‐1C rats but alleviated by CT extract or losartan treatment ( P  < 0.05). Increases in superoxide production and lipid peroxidation were attenuated in 2K‐1C rats treated with CT extract or losartan compared with the untreated group ( P  < 0.05). Increased plasma concentration of nitric oxide metabolites was found in hypertensive rats that received CT extract or losartan. CT extract or losartan suppressed the overexpression of Ang II receptor subtype I (AT1 ‐R) and transforming growth factor‐ β 1 (TGF‐ β 1) in 2K‐1C rats. CONCLUSION: CT extract had antihypertensive effects that were associated with improving vascular function and cardiac hypertrophy in 2K‐1C rats. The mechanisms involved suppression of the renin–angiotensin system, of oxidative stress, and of the AT1 R/TGF‐ β 1 cascade. © 2021 Society of Chemical Industry.